Evangélisme et politique dans la jeune République - Lucia Bergamasco (Transatlantica)
Since the emergence of ethno‑historical studies in the 1960s and 70s suggesting a link between religious affiliation and electoral behavior during the early republic and the antebellum period, historiographies of religious and political culture have both expanded and merged. Today we see the conflation of hitherto separate historiographical trends : namely, the study of the evangelical movement, of its radical abolitionist wing, and of the changing political attitudes of the Americans before the Civil War.